Implementasi Program Sekolah Berakhlak Mulia di SDN 3 Sukapura Probolinggo melalui Pembiasaan Nilai Islami dalam Kegiatan Harian - Muhammad Taufiq (Filantropis: Jurnal Pengabdian kepada Masyarakat, 2025)
The Noble Moral School Program at SDN 3 Sukapura, Probolinggo, aims to strengthen character education by instilling Islamic values ​​in students' daily activities. This program was motivated by the lack of discipline and role models in elementary schools. The implementation method used a participatory approach through outreach, teacher training, mentoring, and evaluation. The program's results demonstrated an increase in students' religious behavior, discipline, responsibility, and politeness, along with a growing awareness of teachers as moral role models. The school environment became cleaner, more harmonious, and more religious. This program reinforces the theory of Islamic character education and habits and can serve as a model for replication in developing a generation of noble morals in other elementary schools.